Synthesis of new polymeric resin and its application in solid phase extraction of copper in water samples using STAT-FAAS - Timur, Irfan; Senkal, B. Filiz; Kaplan, Olcay; Kaya, Gokce; Ozcan, Cemile; Karaaslan, Nagihan M.; Yaman, Mehmet (My University, 2009)
In this study, thiol-containing sulfonamide resin was synthesized, characterized, and applied as a new sorption material, for the determination of copper in water samples. The method, solid phase extraction, is based on the sorption of Cu ions on the synthesized resin without using any complexing reagent. The optimization of experimental conditions was performed by changing parameters including pH, contact time, initial sample volume, and volume of eluent. Flame atomic absorption spectrometry (FAAS) was used for the determinations. The optimized method includes advantages such as a rapid and simple preconcentration step compared to other similar methods because there is no need for a complexing reagent, and the optimum pH of the solution is found in acidic media (pH=3). In brief, 120-fold improvements in the sensitivity of FAAS were achieved by combining slotted tube atom trap-atomic absorption spectrometry (STAT-FAAS) and the optimized preconcentration method. To examine the reliability, the method was checked by using both standard reference materials and ICP-MS measurements. The Cu concentrations in the water samples were found to be in the range of 0.9-13.0 ng mL-1.